Psychological Operations as Non-Kinetic Strategy in Countering Banditry: Insights from the Nigerian Military’s Approach - Kwede , Cornelius Ishaya; Danbala, Ibrahim Nuaimu (Kashere Journal of Politics and International Relations, 2024)
The persistent challenge of banditry in North West Nigeria has compelled the Nigerian military to explore innovative non-kinetic strategies to complement its conventional counterinsurgency efforts. This study examines the role of psychological operations (PSYOPS) as a critical non-kinetic approach employed by the Nigerian military in countering the threat of banditry, drawing on the theoretical framework of soft power. As conceptualised by Joseph Nye, soft power emphasises the ability to shape the preferences and behaviours of target audiences through attraction and co-option rather than coercion. The Paper relied on books, internet materials, and newspapers to access information and analyse the issues raised. Analysis of official military documents and reports and examining relevant media coverage and social media data also provided reliable information. The study explores the planning, implementation, and evaluation of PSYOPS campaigns and their impact on local communities and the overall counter-banditry efforts. The findings show that the Nigerian military's PSYOPS strategy has been instrumental in shaping target audiences' perceptions, attitudes, and behaviours, complementing its kinetic operations and enhancing the effectiveness of its counter banditry approach. The study highlights the strategic value of soft power and PSYOPS in addressing the complex socio-political and psychological dimensions of the banditry problem and recommends that the military should prioritise strategic communication as a core component of its PSYOPS strategy, leveraging various media platforms and channels to disseminate narratives that undermine the legitimacy and appeal of banditry, while promoting the military's legitimacy and the government's commitment to addressing the crisis.